Comparative Effectiveness of Midazolam, Propofol, and Dexmedetomidine in Patients With or at Risk for Acute Respiratory Distress Syndrome: A Propensity Score-Matched Cohort Study - Hu, An-Min; Zhong, Xiong-Xiong; Li, Zhen; Zhang, Zhong-Jun; Li, Hui-Ping (Frontiers in Pharmacology, 2021)
BACKGROUND: Sedatives are commonly used in patients with or at risk for acute respiratory distress syndrome (ARDS) during mechanical ventilation. To systematically compare the outcomes of sedation with midazolam, propofol, and dexmedetomidine in patients with or at risk for ARDS. METHODS: We developed a dataset of real-world data to enable the comparison of the effectiveness and safety of sedatives and the associated outcomes from the MIMIC-III database and the eICU Collaborative Research Database. We performed a systematic study with six cohorts to estimate the relative risks of outcomes among patients administered different sedatives. Propensity score matching was performed to generate a balanced 1:1 matched cohort and to identify potential prognostic factors. The outcomes included hospital mortality, duration of mechanical ventilation, length of ICU stay, length of hospitalization, and likelihood of being discharged home. RESULTS: We performed 60 calibrated analyses among all groups and outcomes with 17,410 eligible patients. Sedation with dexmedetomidine was associated with a lower in-hospital mortality rate than sedation with midazolam and propofol or sedation without dexmedetomidine (P<0.001). When compared with no sedation, the use of midazolam, propofol or dexmedetomidine was associated with a longer ICU stay and longer hospitalization duration (P<0.01). Patients treated with midazolam were relatively less likely to be discharged home (P<0.05). CONCLUSIONS: Patients treated with dexmedetomidine had a reduced risk of mortality. These data suggest that dexmedetomidine may be the preferred sedative in patients with or at risk for ARDS."